2020
DOI: 10.1021/acs.jmedchem.0c00463
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Structural Optimization of 4-(Aminomethyl)benzamides as Potent Entry Inhibitors of Ebola and Marburg Virus Infections

Abstract: The recent Ebola epidemics in West Africa underscore the great need for effective and practical therapies for future Ebola virus outbreaks. We have discovered a new series of remarkably potent small molecule inhibitors of Ebola virus entry. These 4-(aminomethyl)­benzamide-based inhibitors are also effective against Marburg virus. Synthetic routes to these compounds allowed for the preparation of a wide variety of structures, including a conformationally restrained subset of indolines (compounds 41–50). Compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 46 publications
0
16
0
1
Order By: Relevance
“…For studies of other highly pathogenic enveloped viruses such as HIV, H5N1 and EBOV/MARV, this obstacle has been circumvented by a surrogate pseudovirus (PsV) system, which can be widely utilized to not only identify antiviral agents but also study the entry mechanisms [ [33] , [34] , [35] ]. It has been proved that viral PsV systems for CoVs such as SARS-CoV and MERS-CoV are also valid surrogate assays [ 36 , 37 ]. Based on our previous study [ 13 ], we utilized a robust HIV pseudotype model with the SARS-CoV-2-S to screen the OA triterpenoids library for discovering entry inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…For studies of other highly pathogenic enveloped viruses such as HIV, H5N1 and EBOV/MARV, this obstacle has been circumvented by a surrogate pseudovirus (PsV) system, which can be widely utilized to not only identify antiviral agents but also study the entry mechanisms [ [33] , [34] , [35] ]. It has been proved that viral PsV systems for CoVs such as SARS-CoV and MERS-CoV are also valid surrogate assays [ 36 , 37 ]. Based on our previous study [ 13 ], we utilized a robust HIV pseudotype model with the SARS-CoV-2-S to screen the OA triterpenoids library for discovering entry inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“… 117 Using various filoviral replication-defective and replicative infectivity assays, Gaisina et al discovered compounds sharing a common 4-(aminomethyl)benzamide core with broad spectrum activity against both EBOV (Mayinga) and MARV (Angola). 118 In addition to low micromolar potency (EC 50 < 1 μM), these compounds (exemplified by 23 ) exhibited favorable pharmacokinetic and pharmacological properties without detected cytotoxicity. Preliminary mechanistic studies suggested that the inhibitory activity of these compounds resulted from the direct binding and inhibition of the EBOV envelope glycoprotein (GP) protein, clearly indicating GP as an attractive target for therapeutic intervention other than the key immunogen for eliciting antibody responses.…”
Section: Ebolavirus (Ebov)mentioning
confidence: 99%
“…These mechanisms were also dependent on the interaction of hormones with their receptors. The inhibitory effect of estrogens on replication was documented [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ]. in a panel of viruses (for particulars see Table 1 ).…”
Section: Effect Of Oestrogen Receptor Modulators (Erms) On Viral Replicationmentioning
confidence: 99%